Assessing the Flood and Riverbank Erosion Impacts and Coping Strategies in Hatia Union of Ulipur, Kurigram, Bangladesh: Assessing the Flood and Riverbank Erosion Impacts (Journal of the Asiatic Society of Bangladesh, Science, 2025)
The present paper aims to focus on the flood and riverbank erosion impacts and coping strategies in Hatia Union of Ulipur, Kurigram of Bangladesh. Due to the prevailing geographical location and topographical features, Bangladesh is considered as one of the most disaster-prone countries in the world. Kurigram district, located in the northern part of Bangladesh, is particularly flood and riverbank erosion prone because of its extensive river networks and its location within the Teesta-Brahmaputra River basin. Hatia Union of Ulipur Upazila was chosen as the study area due to its susceptibility to these disasters. In order to identify the flood and riverbank erosion impacts and coping strategies, field level data and information were collected through field survey and interviewing the respondents. Using ArcGIS Pro software, Sentinel-1 (SAR) and LANDSAT images with a resolution of 30 meters, the flood and riverbank erosion maps were produced. Floods and riverbank erosion both have significant impacts on local communication, food, shelter, health, employment, security, and people’s movement. Local people suffer a lot and their lives and livelihoods are affected severely by these disaster events. The affected communities undertake various coping strategies with the support of governmental and non-governmental organizations to overcome the incumbent impacts of flood and riverbank erosion. Policy level development and effective implementation of various projects and programs prioritizing the most vulnerable areas, focusing on socio-economic advancement, and resolving relevant issues can limit the sufferings of local people.J. Asiat. Soc. Bangladesh, Sci. 50(1-2): 69-88, June-December 2024